2018
DOI: 10.1177/0956797617703667
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Rich False Memories of Committing Crime: Commentary on Shaw and Porter (2015)

Abstract: For 20 years, scientists have created a vast range of false autobiographical memories. Variations of the powerful "lost-in-the-mall" paradigm have led ordinary adults to appear to remember nonexistent childhood hospital visits, animal attacks, classroom pranks, and hot-air balloon rides (for a summary, see Newman & Garry, 2013). An analysis of published lost-in-the-mall studies suggests that, over time, the overall rate of false beliefs-but not false memories-generated in these studies has increased (see Fig. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 27 publications
1
47
0
1
Order By: Relevance
“…In our analyses comparing memories, those who reported a belief that an event had happened, but not a memory, were excluded (unless otherwise stated). This mirrors the classification used in our original study (Murphy et al, 2019) and is motivated by a need to clearly discriminate between memories and mere beliefs (Wade et al, 2018). Across the entire sample, 22% of participants reported a false memory; 17% reported a false memory for one fabricated story and 5% reported a false memory for both of the fabricated stories shown.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…In our analyses comparing memories, those who reported a belief that an event had happened, but not a memory, were excluded (unless otherwise stated). This mirrors the classification used in our original study (Murphy et al, 2019) and is motivated by a need to clearly discriminate between memories and mere beliefs (Wade et al, 2018). Across the entire sample, 22% of participants reported a false memory; 17% reported a false memory for one fabricated story and 5% reported a false memory for both of the fabricated stories shown.…”
Section: Resultsmentioning
confidence: 86%
“…Though research has shown that misinformation can be difficult to correct (Lewandowsky et al, 2012), continuing participants were in fact slightly less likely to fall for the fake news story concerning illegal posters than newly recruited participants. This was true whether we assessed reported memories only, or included mere beliefs in a less conservative classification of memory (Wade et al, 2018). Amongst continuing participants, there was no increase in false memories for those who saw the same version of the poster story (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In sum, the risks of distorting memories of personally experienced events, or developing false memories of entire events (or at least false beliefs that these events occurred, see the distinction in Wade et al, 2018) might be high when suggestive techniques are used to recover or modify traumatic memories for therapeutic purposes. These risks could be all the higher as therapists and/or patients believe in the reality of repressed memories.…”
Section: Recovered Memory Therapy and Beliefs About Repressed Memorymentioning
confidence: 99%
“…The false memories involved accounts of emotional or criminal events from the participants' adolescence, the events allegedly happened between the ages of 11 and 14, and those recalling them were on average 20 years old. All videos included were also classified as false memories in the Shaw and Porter data re-analysis by Wade et al (2018). For a discussion of this coding disagreement see Shaw (2018).…”
Section: Study 1 and Studymentioning
confidence: 99%